Analisis Korespondensi dalam Studi Transformasi Adaptif Arsitektur Permukiman Tepian Sungai - Hamdil Khaliesh; Zairin Zain (Universitas Muhammadiyah Palembang, 2025)
This study examines adaptive transformation in riverbank settlements along the Kapuas River in Pontianak, focusing on socioeconomic factors that influence community adaptation in Kampung Kamboja, Kampung Tambelan, and Kampung Beting. Using a quantitative explanatory approach, this study applies Correspondence Analysis to analyze the relationship between location and settlement adaptation characteristics. The findings show that dominant factors driving physical changes in housing include family expansion, the orientation of walkways (gertak), and building damage. Economic limitations and strong social bonds also play significant roles, alongside government policy support in riverbank areas aimed at promoting a tourist village program. The Correspondence Analysis method helps identify the most influential factors in a measurable and specific way, enhancing insights into varied adaptation patterns. This study contributes to the development of quantitative methods for understanding settlement adaptation dynamics while providing a foundation for sustainable riverbank area preservation and development planning